2017
DOI: 10.1111/jne.12532
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hypothalamic corticotropin‐releasing hormone neurone excitability by oxytocin

Abstract: Oxytocin (OT) is a neuropeptide that exerts multiple actions throughout the brain and periphery. Within the brain, OT regulates diverse neural populations, including neural networks controlling responses to stress. Local release of OT within the paraventricular nucleus (PVN) of the hypothalamus has been suggested to regulate stress responses by modulating the excitability of neighbouring corticotropin-releasing hormone (CRH) neurones. However, the mechanisms by which OT regulates CRH neurone excitability are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 53 publications
(130 reference statements)
2
21
0
Order By: Relevance
“…By contrast to our expectations, we were unable to produce reliable tonic inhibition of PVN CRH neurones using bath application of either oxytocin or TGOT at concentrations between 20 and 600 nmol L −1 in either control or salt‐loaded animals. In that respect, our results are consistent with another recent study reporting that bath application of 1 µmol L −1 oxytocin had no direct effect on PVN CRH neurones . To reduce the possibility that bath application was leading to rapid receptor desensitisation and/or internalisation, we attempted to directly activate PVN CRH neurones by locally applying OT via a picospritzer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By contrast to our expectations, we were unable to produce reliable tonic inhibition of PVN CRH neurones using bath application of either oxytocin or TGOT at concentrations between 20 and 600 nmol L −1 in either control or salt‐loaded animals. In that respect, our results are consistent with another recent study reporting that bath application of 1 µmol L −1 oxytocin had no direct effect on PVN CRH neurones . To reduce the possibility that bath application was leading to rapid receptor desensitisation and/or internalisation, we attempted to directly activate PVN CRH neurones by locally applying OT via a picospritzer.…”
Section: Discussionsupporting
confidence: 91%
“…In that respect, our results are consistent with another recent study reporting that bath application of 1 µmol L −1 oxytocin had no direct effect on PVN CRH neurones. 38 To reduce the possibility that bath application was leading to rapid receptor desensitisation and/or internalisation, [39][40][41][42] we attempted to directly activate PVN CRH neurones by locally applying OT via a picospritzer. These experiments also failed to produce a clear or reliable immediate response to oxytocin application; however, we did note a small yet statistically significant increase in current density over time when oxytocin was applied in this manner (1 second 5-Hz train of 10-msec puffs delivered every 30 seconds, with 1 µmol L −1 oxytocin in the pipette).…”
Section: Discussionmentioning
confidence: 99%
“…Microinjection of oxytocin into the hypothalamic paraventricular nucleus has been reported to reduce stress responses of anxiety-related behaviours and the hypothalamic-adrenal axis, whereas that of an oxytocin antagonist impairs the social buffering actions on behavioural and neuroendocrine responses in female prairie voles. 93 These findings suggest that oxytocin suppresses the activity of hypothalamic CRH neurones also by suppressing excitatory synaptic transmission onto CRH neurones presynaptically. Pharmacological blockade of the GABA A receptor has been reported to block the actions of oxytocin in prairie voles.…”
Section: Hypothalamic Paraventricular Nucleusmentioning
confidence: 93%
“…In contrast to the hypothalamus, where OT was shown to regulate CRF neurons’ activity and expression (Nomura et al, 2003; Bulbul et al, 2011; Jurek et al, 2015; Jamieson et al, 2017), and CRF receptors were shown to interact with OT secretion (Bruhn et al, 1986; Arima and Aguilera, 2000; Dabrowska et al, 2011), very little is known about the functional interaction between OT and CRF in the extra-hypothalamic limbic systems critical for the regulation of fear and anxiety-like behavior.…”
Section: Role Of the Bed Nucleus Of The Stria Terminalis (Bnst) In Thmentioning
confidence: 99%
“…However, evidence for direct interaction of OT with the CRF neurons in the BNST has not been yet found, but see (Jurek et al, 2015; Jamieson et al, 2017) for OT-CRF interaction in the PVN. Further, potential mechanism of how OTR in the BNST dl may differentially modulate cued and non-cued fear remains unknown.…”
Section: Role Of the Bed Nucleus Of The Stria Terminalis (Bnst) In Thmentioning
confidence: 99%